2020
DOI: 10.21203/rs.3.rs-80071/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diastolic Dysfunction and Impaired Cardiac Output Reserve in Dysmetabolic Nonhuman Primate With Proteinuria

Abstract: Background Cardiorenal complications are common in patients with dysmetabolism and diabetes. The present study aimed to examine if a nonhuman primate (NHP) model with spontaneously developed metabolic disorder and diabetes develops similar complications to humans, such as proteinuria and cardiac dysfunction at resting condition or diminished cardiac functional reserve following dobutamine stress echocardiography (DSE).Methods and Results A total of 66 dysmetabolic and diabetic cynomolgus (Macaca fascicu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…This observation is consistent with the previous nding in db/db mice that FTY720 led to sustained normalization of hyperglycemia, which was also remained for life even after withdrawal of FTY20 11 . The animal model used in the present study is well-characterized naturally occurred diabetic NHPs with all the T2D characteristics in human patients at different stages of the disease progression and is by far the most predictive translational animal model for human metabolic syndrome, including diabetes [19][20][21][22][23][24][25] . To our knowledge, FTY720 is the only compound with a sustained anti-glycemic effect even after cease of the treatment in both the diabetic mice and NHPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is consistent with the previous nding in db/db mice that FTY720 led to sustained normalization of hyperglycemia, which was also remained for life even after withdrawal of FTY20 11 . The animal model used in the present study is well-characterized naturally occurred diabetic NHPs with all the T2D characteristics in human patients at different stages of the disease progression and is by far the most predictive translational animal model for human metabolic syndrome, including diabetes [19][20][21][22][23][24][25] . To our knowledge, FTY720 is the only compound with a sustained anti-glycemic effect even after cease of the treatment in both the diabetic mice and NHPs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the diabetic NHPs had the compromised cardiac functions, particularly, the LV systolic functions measured by reduced ejection fraction (EF) and fractional shortening (FS) 20,27 . In the present study, the standard echocardiography was performed in the anesthetized diabetic NHPs before (baseline) and 9 weeks after (post-dose) administration of vehicle or FTY720 (5 mg/kg, PO, QD).…”
Section: Fty720 Enhanced Cardiac Left Ventricular (Lv) Systolic Functmentioning
confidence: 99%
See 1 more Smart Citation
“…The echocardiography revealed that the ejection fraction (EF) is significantly reduced from 68% in the T A B L E 1 General characteristics of the diabetic NHPs following once daily oral administration of vehicle (purified water, 1 ml/kg) or FTY720 ( normal NHPs to 62% in the diabetic NHPs and fractional shortening (FS) from 43% to 30% [17,21]. In the present study, the echocardiography was performed in the anesthetized diabetic NHPs before (baseline) and 8 weeks after administration of the vehicle or FTY720.…”
Section: Fty720 Enhanced Cardiac Left Ventricular (Lv) Systolic Funct...mentioning
confidence: 99%
“…With the limitations of the rodent models of diabetes, from which the experiment results often are unable to translate to human diseases, the present study aimed to further explore the therapeutic potential of FTY720 in the treatment of T2D using a nonhuman primate (NHP) model with spontaneously developed diabetes, which has been proved to be highly resemble all the characteristics of T2D in human patients at different stages of the disease progression, and is widely used in academia and pharmaceutical industry as by far the most predictive animal model for both the basic and preclinical research in testing novel therapeutics for human metabolic diseases, including diabetes [17][18][19][20][21][22]. Interestingly, the spontaneous diabetes NHPs clearly showed β-cell failure in response to glucose stimulation [20], thus, the findings in this well-characterized naturally occurred diabetic model can provide significant insight information for development of FTY720 as a therapeutic drug for the treatment of T2D in human patients.…”
mentioning
confidence: 99%